High-compaction lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery
By optimizing the particle size grading of the precursor of lithium iron phosphate positive electrode material and nitrogen-doped graphene treatment during secondary sintering, the high manufacturing cost and grading problems of the positive electrode material of lithium-ion battery are solved, and the conductivity and cycling performance of the battery are improved.
Patent Information
- Application Number
- CN202510761209.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-24
- Filing Date
- 2025-06-09
- Publication Date
- 2025-08-29
AI Technical Summary
The manufacturing cost of existing lithium-ion battery cathode materials is high, and it is difficult to achieve the theoretical proportion of particle grade distribution, which affects battery performance.
By optimizing the particle size grading of the two precursors and using C3N4 to form nitrogen-doped defective graphene during the secondary sintering process, the conductivity and cycling performance are improved.
It achieves better particle grading and roundness, improves the conductivity and cycling performance of the material, and reduces manufacturing costs.
Smart Images

Figure CN120553664A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a high-density lithium iron phosphate cathode material, a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries are widely used due to their high energy density, lack of memory effect, and long cycle life. The cathode material of lithium-ion batteries is crucial to their performance and application scenarios. Olivine-structured lithium iron phosphate (LIFP) has become a strong competitor in power batteries due to its high voltage, high capacity ratio, long cycle life, high safety, and low cost. As consumers' demands for safety continue to rise, LFP has once again become the preferred choice for automakers.
[0003] Compared with the traditional two-step process, in which the same precursor is used for both large and small particle precursors, the material melts and grows significantly during the secondary calcination process, making it difficult to achieve the theoretical large and small particle grading ratio. At the same time, the existing secondary calcination process uses the iron phosphate method or the more expensive ferrous oxalate method or liquid phase method, which increases manufacturing costs. Summary of the Invention
[0004] The present invention provides a high-density lithium iron phosphate cathode material, a preparation method thereof, and a lithium-ion battery to address the deficiencies of the above-mentioned prior art. By optimizing the particle size grading of the two precursors, the particles of the two precursors obtained have better roundness. In addition, the conductivity and cycle performance of the lithium iron phosphate cathode material are improved by re-firing.
[0005] In order to achieve the purpose of the present invention, the following technologies are proposed: A first aspect provides a method for preparing a high-density lithium iron phosphate positive electrode material, comprising the steps of: Step 01: mixing ferrous phosphate, lithium phosphate, an elemental supplement, a first carbon source, a first dopant, and deionized water, and sequentially performing wet grinding, spray drying, sintering, and air flow milling to obtain first granular lithium iron phosphate; Step 02: mixing in-situ doped iron phosphate, lithium carbonate, a second carbon source, and deionized water, and sequentially performing wet grinding, spray drying, sintering, and air flow milling to obtain second granular lithium iron phosphate; The particle size of the first granular lithium iron phosphate obtained in step 01 is larger than the particle size of the second granular lithium iron phosphate obtained in step 02; Step 03, mixing the first granular lithium iron phosphate obtained in step 01, the third carbon source, and deionized water, and obtaining a first slurry by wet grinding; The second granular lithium iron phosphate obtained in step 02, the fourth carbon source, and deionized water are mixed and wet-grinded to obtain a second slurry; Step 04: Mix the first slurry and the second slurry obtained in step 03, and sequentially perform spray drying, sintering, and air flow milling to obtain a lithium iron phosphate positive electrode material.
[0006] Furthermore, in step 01: The Fe / P molar ratio in ferrous phosphate is 1.42 to 1.48, and the specific surface area of ferrous phosphate is 20 m 2 / g to 40m 2 / g; The amount of lithium phosphate added is such that the Li / Fe molar ratio is maintained at 1.03 to 1.07, and the purity of the lithium phosphate is ≥98%; The elemental supplement is one of lithium carbonate and phosphoric acid, with the purity of lithium carbonate being ≥99.5% and the purity of phosphoric acid being 85%; The Fe / P molar ratio of the first granular lithium iron phosphate is 0.965; The first carbon source is a combination of one or more of glucose, sucrose, and polyethylene glycol, and the amount of the first carbon source added is 0.4 wt% to 0.8 wt% of the carbon content in the first granular lithium iron phosphate; The first dopant is one or more of titanium dioxide, ammonium metavanadate, manganese pentoxide, niobium pentoxide and cerium oxide. The amount of the first dopant added is determined according to the proportion of one or more of titanium, vanadium, manganese, niobium and cerium elements in the first dopant in the first granular lithium iron phosphate being 3000ppm to 5000ppm.
[0007] Furthermore, in step 01: When wet grinding, it is carried out at 10°C to 45°C, the sand grinding particle size D50 is 0.7μm to 0.9μm, and the solid content is 30wt% to 50wt%; During spray drying, the feed temperature is 180°C to 240°C, the discharge temperature is 80°C to 140°C, the particle size D50 of the intermediate product obtained after spray drying is 20μm to 60μm, and the water content is ≤1.5%; During sintering, the sintering temperature is 780°C to 810°C and the sintering time is 6h to 10h under nitrogen atmosphere; The particle size D50 of the first lithium iron phosphate particles is 2.0 μm to 4.0 μm, and the average particle size of the first lithium iron phosphate particles is 2000 nm to 3000 nm.
[0008] Furthermore, in step 02: The Fe / P molar ratio of the in-situ doped iron phosphate is 0.970 to 0.980, and the specific surface area of the in-situ doped iron phosphate is 15m 2 / g to 25m 2 / g, the primary particle size of the in-situ doped iron phosphate is 40nm to 80nm; The doping element is Ti, and the in-situ doping amount of Ti is 5000ppm to 8000ppm; The purity of lithium carbonate is ≥99.5%, and the Li / Fe molar ratio of lithium carbonate is 1.01 to 1.04; The second carbon source is a mixture of one or more of glucose, sucrose, polyethylene glycol, and citric acid and one of urea, melamine, dicyandiamide, and thiourea, wherein the amount of the second carbon source added is 0.8 wt % to 1.2 wt % of the carbon content in the second granular lithium iron phosphate; Urea, melamine, dicyandiamide and thiourea are all raw materials of C3N4, and the carbon content in C3N4 accounts for 0.4wt% of the carbon content in the second granular lithium iron phosphate.
[0009] Furthermore, in step 02: Wet grinding is carried out at 10°C to 45°C, with a sand grinding particle size D50 of 0.15μm to 0.25μm and a solid content of 30wt% to 50wt%; The feed temperature of the spray drying is 180°C to 240°C, the discharge temperature is 80°C to 140°C, and the particle size D50 of the intermediate product obtained by the spray drying is 20 μm to 60 μm, and the water content is ≤1.5%; The sintering is carried out in a nitrogen atmosphere, the sintering temperature is 500° C. to 600° C., and the sintering time is 3 h to 7 h; The particle size D50 of the second granular lithium iron phosphate obtained after the airflow milling is 0.4 μm to 0.6 μm, and the average particle size of the second granular lithium iron phosphate is 80 nm to 160 nm.
[0010] Furthermore, in step 03: The third carbon source and the fourth carbon source are both polyvinyl pyrrolidone, and the addition amount of the third carbon source and the fourth carbon source accounts for 1.1wt% to 1.5wt% of the carbon content in the lithium iron phosphate positive electrode material; The wet grinding of the first slurry and the second slurry is carried out at 10° C. to 45° C., with a solid content of 30 wt % to 50 wt %, a sanding particle size D50 of the first slurry of 0.7 μm to 1.0 μm, and a sanding particle size D50 of the second slurry of 0.10 μm to 0.20 μm.
[0011] Furthermore, in step 04, the mass ratio of the first slurry to the second slurry is 5 to 7:3 to 5.
[0012] Furthermore, in step 04: The feed temperature of the spray drying is 180°C to 240°C, the discharge temperature is 80°C to 140°C, the particle size of the intermediate product is 20μm to 60μm, and the water content is ≤1.5%; The sintering process is carried out in a nitrogen atmosphere, the sintering temperature is 760°C to 780°C, and the sintering time is 6h to 8h; The particle size D50 of the lithium iron phosphate positive electrode material obtained after airflow milling is 0.9 μm to 1.2 μm.
[0013] The second aspect provides a lithium iron phosphate positive electrode material, which is prepared by a preparation method of a high-density lithium iron phosphate positive electrode material.
[0014] A third aspect provides a lithium-ion battery, which includes: a battery positive electrode made of lithium iron phosphate positive electrode material.
[0015] The advantages of the above technical solution are: First, the present invention combines the advantages of ferrous phosphate process and ferric phosphate process, and uses C3N4 to coat the second granular lithium iron phosphate, which can effectively reduce particle fusion, make the gradation of the finished lithium iron phosphate positive electrode material better, and make the particles more rounded.
[0016] Secondly, during the secondary grinding process of the second granular lithium iron phosphate, the present invention peels off the blocky C3N4 into g-C3N4, and at the same time converts the g-C3N4 into nitrogen-doped defective graphene through the second sintering, thereby improving the conductivity of the material.
[0017] Finally, the present invention utilizes high molecular nitrogen-containing organic matter as a carbon source to form a nitrogen-doped carbon layer, thereby improving the density of the surface-coated carbon layer, inhibiting side reactions, and improving cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0019] Figure 1 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention.
[0020] Figure 2 This is a charge and discharge performance curve of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0021] Example 1 A method for preparing a high-density lithium iron phosphate positive electrode material comprises the following steps: Step 01: 1000 g of Fe / P with a molar ratio of 1.45 and a specific surface area of 30 m 2 / g of ferrous phosphate, 241.0g of lithium phosphate, and 2.24g of lithium carbonate were mixed. 44.37g of sucrose, 5.03g of titanium dioxide, 2.46g of ammonium metavanadate, and 1855g of water were added and mixed in a ball mill to form a dispersion. The dispersion was transferred to a sand mill controlled at 25°C and ground to a particle size D50 of 0.8μm and a solid content of 40wt%, to produce a slurry. The slurry was spray-dried with an inlet air temperature of 210°C and an outlet air temperature of 110°C. After granulation, a precursor powder with a particle size D50 of 40μm and a moisture content of ≤1.5% was obtained. The resulting precursor powder was calcined at 795°C for 5 hours using nitrogen as a protective atmosphere. The sintered material was pulverized using a gas jet to a particle size D50 of 3.0μm and an average particle size of 2500nm during pulverization, producing the first granular form of lithium iron phosphate.
[0022] Step 02: 1000 g of Fe / P with a molar ratio of 0.975 and a specific surface area of 20.0 m 2 / g of ferric phosphate with an in-situ Ti doping level of 6000ppm and a primary particle size of 60nm and 252.35g of lithium carbonate were mixed. 50g of glucose, 60g of citric acid, 80g of melamine, and 1878g of water were added and mixed in a ball mill to form a dispersion. The dispersion was transferred to a sand mill controlled at 25°C and ground to a particle size D50 of 0.20μm and a solid content of 40wt%, yielding a slurry. The slurry was spray-dried with an inlet air temperature of 210°C and an outlet air temperature of 110°C, and granulated to produce a precursor powder with a particle size D50 of 40μm and a moisture content of ≤1.5%. The resulting precursor powder was calcined at 550°C for 4 hours in a nitrogen atmosphere. The sintered material was air-stream milled to a particle size D50 of 0.5μm, yielding a second granular form of lithium iron phosphate.
[0023] Step 03, take 1000g of the first granular lithium iron phosphate prepared in step 01, add 20g of polyvinyl pyrrolidone and 1500g of water, and mix in a ball mill to form a dispersion. Transfer the dispersion to a sand mill controlled at 25°C for grinding, with a sand milling particle size D50 of 0.85μm and a solid content of 40wt%, to obtain a first slurry. Take 1000g of the second granular lithium iron phosphate prepared in step 02, add 20g of polyvinyl pyrrolidone and 1500g of water, and mix in a ball mill to form a dispersion. Transfer the dispersion to a sand mill controlled at 25°C for grinding, with a sand milling particle size D50 of 0.15μm and a solid content of 40wt%, to obtain a second slurry.
[0024] In step 4, the first slurry and the second slurry prepared in step 3 are mixed in a mass ratio of 6:4. The mixed slurry is spray-dried with the inlet air temperature controlled at 210°C and the outlet air temperature at 110°C. The granulation is performed to produce a sintered precursor powder with a particle size D50 of 40 μm and a moisture content of ≤1.5%. The sintered precursor powder is calcined at 770°C for 7 hours using nitrogen as the protective atmosphere. The sintered material is pulverized to a particle size D50 of 1.1 μm to produce a lithium iron phosphate cathode material.
[0025] The microstructure morphology of the prepared lithium iron phosphate cathode material was observed, as shown in Figure 1 As shown in the figure, it is not difficult to see that the first granular lithium iron phosphate and the second granular lithium iron phosphate are evenly distributed, and the roundness of the particles is excellent. The mechanism is explored because this embodiment uses high molecular nitrogen-containing organic matter and g-C3N4 as carbon sources to form a nitrogen-doped carbon layer and a defective graphene carbon layer, which improves the density of the surface-coated carbon layer, inhibits side reactions, reduces the interface resistance, and significantly improves the cycle performance.
[0026] In addition, in order to further verify its application performance in the battery, the battery prepared in Example 1 was tested for charge and discharge performance. The test curve is shown in FIG. Figure 2 As shown in the figure, it can be seen that the main discharge platform of the battery is about 3.4V, and the capacity of the platform area exceeds 150mAh / g. Therefore, it is shown that the battery processed by the lithium iron phosphate positive electrode material prepared in this embodiment has a stable two-phase reaction mechanism. The main reason for this result is that the lithium iron phosphate positive electrode material has a uniform particle structure, thereby reducing local polarization. In addition, since the end point of the curve is 160mAh / g, it is known that the utilization rate of the lithium iron phosphate positive electrode material is high. And since the average voltage in the platform area of the battery is about 3.4V, it is known that the energy density is approximately equal to 3.4V×160mAh / g=544Wh / kg, which shows that its energy density is high. In addition, since the voltage fluctuation in the platform area of the battery is small (ΔV<0.2V), it shows that the electrode / electrolyte interface impedance is low.
[0027] Example 2 A method for preparing a high-density lithium iron phosphate positive electrode material comprises the following steps: Step 01: 1000 g of Fe / P with a molar ratio of 1.48 and a specific surface area of 40 m 2 / g of ferrous phosphate, 243.64g of lithium phosphate, and 11.93g of phosphoric acid were mixed. 37.2g of sucrose, 3.34g of titanium dioxide, 2.51g of ammonium metavanadate, and 2900g of water were added and mixed in a ball mill to form a dispersion. The dispersion was transferred to a sand mill controlled at 10°C and ground to a particle size D50 of 0.7μm and a solid content of 30wt%, to obtain a slurry. The slurry was spray-dried with an inlet temperature of 180°C and an outlet temperature of 80°C, and granulated to obtain a precursor powder with a particle size D50 of 20μm and a moisture content of ≤1.5%. The resulting precursor powder was calcined at 780°C for 10 hours using nitrogen as the protective atmosphere. The sintered material was pulverized to a particle size D50 of 2.0μm and an average primary particle size of 2000nm, producing the first granular lithium iron phosphate.
[0028] Step 02: 1000 g of Fe / P with a molar ratio of 0.980 and a specific surface area of 25.0 m 2 / g of ferric phosphate with an in-situ Ti doping level of 5000ppm and a primary particle size of 40nm and 248.66g of lithium carbonate were mixed. 30g of glucose, 38g of polyethylene glycol, 80g of melamine, and 2900g of water were added and mixed in a ball mill to form a dispersion. The dispersion was transferred to a sand mill controlled at 25°C to a particle size D50 of 0.15μm and a solid content of 30wt%, yielding a slurry. The slurry was spray-dried with an inlet temperature of 180°C and an outlet temperature of 80°C to produce a precursor powder with a particle size D50 of 20μm and a moisture content of ≤1.5%. The resulting precursor powder was calcined at 600°C for 3h in a nitrogen atmosphere. The sintered material was pulverized to a particle size D50 of 0.6μm, yielding a second granular form of lithium iron phosphate.
[0029] Step 03, take 1000g of the first granular lithium iron phosphate prepared in step 01, add 20g of polyvinyl pyrrolidone and 2300g of water, and mix them in a ball mill to form a dispersion. Transfer the dispersion to a sand mill controlled at 10°C for grinding, with a sand milling particle size D50 of 0.70μm and a solid content of 30wt%, to obtain a first slurry. Take 1000g of the second granular lithium iron phosphate prepared in step 02, add 20g of polyvinyl pyrrolidone and 2300g of water, and mix them in a ball mill to form a dispersion. Transfer the dispersion to a sand mill controlled at 10°C for grinding, with a sand milling particle size D50 of 0.10μm and a solid content of 30wt%, to obtain a second slurry.
[0030] In step 4, the first slurry and the second slurry obtained in step 3 are mixed in a mass ratio of 7:3. The mixed slurry is spray-dried with the inlet air temperature controlled at 180°C and the outlet air temperature at 80°C. The granulation is performed to obtain a sintered precursor powder with a particle size D50 of 20 μm and a moisture content of ≤1.5%. The sintered precursor powder is calcined at 780°C for 6 hours using nitrogen as the protective atmosphere. The sintered material is air-flow milled to a particle size D50 of 0.9 μm to produce a lithium iron phosphate cathode material.
[0031] Example 3 A method for preparing a high-density lithium iron phosphate positive electrode material comprises the following steps: Step 01: 1000 g of Fe / P with a molar ratio of 1.42 and a specific surface area of 20 m 2 / g of ferrous phosphate, 226.05g of lithium phosphate, and 15.83g of lithium carbonate were mixed. 51.3g of sucrose, 6.66g of titanium dioxide, 2.42g of ammonium metavanadate, and 1220g of water were added and mixed in a ball mill to form a dispersion. The dispersion was transferred to a sand mill controlled at 40°C and ground to a particle size D50 of 0.9μm and a solid content of 50wt%, yielding a slurry. The slurry was spray-dried with an inlet air temperature of 240°C and an outlet air temperature of 140°C, and granulated to obtain a precursor powder with a particle size D50 of 60μm and a moisture content of ≤1.5%. The resulting precursor powder was calcined at 810°C for 6 hours using nitrogen as a protective atmosphere. The sintered material was pulverized to a particle size D50 of 4.0μm and an average primary particle size of 3000nm, yielding the first granular lithium iron phosphate.
[0032] Step 02: 1000 g of Fe / P with a molar ratio of 0.980 and a specific surface area of 15.0 m 2 / g of ferric phosphate with an in-situ Ti doping level of 8000ppm and a primary particle size of 80nm and 256.05g of lithium carbonate were mixed. 52g of sucrose, 35g of polyethylene glycol, 80g of melamine, and 1300g of water were added and mixed in a ball mill to form a dispersion. The dispersion was transferred to a sand mill controlled at 40°C to a particle size D50 of 0.25μm and a solid content of 30wt%, yielding a slurry. The slurry was spray-dried with an inlet temperature of 240°C and an outlet temperature of 140°C, and granulated to obtain a precursor powder with a particle size D50 of 60μm and a moisture content of ≤1.5%. The resulting precursor powder was calcined at 500°C for 7h in a nitrogen atmosphere. The sintered material was pulverized to a particle size D50 of 0.4μm, yielding a second granular form of lithium iron phosphate.
[0033] In step 03, 1000 g of the first granular lithium iron phosphate prepared in step 01 is added to 20 g of polyvinyl pyrrolidone and 1000 g of water in a ball mill to form a dispersion. The dispersion is transferred to a sand mill controlled at 40°C and ground to a particle size D50 of 1.0 μm and a solid content of 50 wt%, to obtain a first slurry. 1000 g of the second granular lithium iron phosphate prepared in step 02 is added to 20 g of polyvinyl pyrrolidone and 1000 g of water in a ball mill to form a dispersion. The dispersion is transferred to a sand mill controlled at 40°C and ground to a particle size D50 of 0.20 μm and a solid content of 50 wt%, to obtain a second slurry.
[0034] In step 4, the first slurry and the second slurry were mixed in a mass ratio of 5:5. The mixed slurry was spray-dried with the inlet air temperature controlled at 240°C and the outlet air temperature at 140°C. The granulation yielded a sintered precursor powder with a particle size (D50) of 60 μm and a moisture content of ≤1.5%. The sintered precursor powder was calcined at 760°C for 8 hours using nitrogen as the protective atmosphere. The sintered material was pulverized to a particle size (D50) of 1.2 μm to produce the lithium iron phosphate cathode material.
[0035] Comparative Example 1 The difference between this comparative example and Example 1 is that in step 01, the raw materials are replaced by ferrous phosphate and lithium phosphate with a Fe / P molar ratio of 0.965, and the grinding D50 particle size is controlled to be 0.4 μm.
[0036] Comparative Example 2 The difference between this comparative example and Example 1 is that: no C3N4 raw material (melamine) is added in step 02, and only 70g of glucose and 65g of citric acid are added as the second carbon source.
[0037] Comparative Example 3 The difference between this comparative example and Example 1 is that in step 03, the third carbon source is 20g glucose + 23g polyethylene glycol.
[0038] Comparative Example 4 The difference between this comparative example and Example 1 is that in step 04, the first slurry and the second slurry are mixed in a ratio of 9:1.
[0039] In order to further verify the lithium iron phosphate positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4 above, tests were performed.
[0040] First, the lithium iron phosphate positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were photographed with a scanning electron microscope at a magnification of 5k to obtain microstructure morphologies.
[0041] Secondly, 1 g of the lithium iron phosphate positive electrode material prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was weighed and placed into a compaction mold, the mold was placed into a compaction device to start testing, and the powder compaction density result was taken under a pressure of 30 KN.
[0042] Then, the lithium iron phosphate positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were dispersed in NMP with Super P and PVDF in a mass ratio of 80:10:10. After ball milling and uniform dispersion, they were coated on aluminum foil and vacuum dried to prepare positive electrode sheets. The electrolyte was 1 mol / L LiPF6, wherein the solvent volume ratio was EC:DMC:EMC=1:1:1 (volume ratio), the separator was Celgard polypropylene film, and the metal lithium sheet was the negative electrode. They were assembled together to form a button half-cell. The test voltage range was 2.0V-3.75V. The battery was charged to 3.75V using a constant current constant voltage charging method and discharged to 2.0V using a constant current discharge method. The charge and discharge current was 0.1C and cycled for 2 cycles. The battery was then cycled for 2 cycles using a 1C charge and discharge current, with the cut-off voltage condition being the same as 0.1C. The lithium iron phosphate materials obtained in Examples 1-3 and Comparative Examples 1-4 were prepared into full batteries, and their cycle performance at room temperature was tested. The test results are shown in Table 1 below.
[0043] Table 1 Test results According to the above results, it can be seen that the lithium iron phosphate positive electrode material prepared in the embodiment of the present invention has higher powder compaction and better capacity.
[0044] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Obviously, those skilled in the art may make various modifications and variations to the present invention without departing from the spirit and scope of the present invention. Therefore, to the extent such modifications and variations fall within the scope of the claims and their equivalents, the present invention is intended to encompass such modifications and variations.
Claims
1. A method for preparing a high-density lithium iron phosphate positive electrode material, characterized in that: Including steps: Step 01: mixing ferrous phosphate, lithium phosphate, an elemental supplement, a first carbon source, a first dopant, and deionized water, and sequentially performing wet grinding, spray drying, sintering, and air flow milling to obtain first granular lithium iron phosphate; Step 02: mixing in-situ doped iron phosphate, lithium carbonate, a second carbon source, and deionized water, and sequentially performing wet grinding, spray drying, sintering, and air flow milling to obtain second granular lithium iron phosphate; The particle size of the first granular lithium iron phosphate obtained in step 01 is larger than the particle size of the second granular lithium iron phosphate obtained in step 02; Step 03, mixing the first granular lithium iron phosphate obtained in step 01, the third carbon source, and deionized water, and obtaining a first slurry by wet grinding; The second granular lithium iron phosphate obtained in step 02, the fourth carbon source, and deionized water are mixed and wet-grinded to obtain a second slurry; Step 04: Mix the first slurry and the second slurry obtained in step 03, and sequentially perform spray drying, sintering, and air flow milling to obtain a lithium iron phosphate positive electrode material.
2. The method for preparing a high-density lithium iron phosphate cathode material according to claim 1, wherein: In step 01: The Fe / P molar ratio in ferrous phosphate is 1.42 to 1.48, and the specific surface area of ferrous phosphate is 20 m 2 / g to 40m 2 / g; The amount of lithium phosphate added ensures that the Li / Fe molar ratio is 1.03 to 1.07, and the purity of lithium phosphate is ≥98%; The elemental supplement is one of lithium carbonate and phosphoric acid, with the purity of lithium carbonate being ≥99.5% and the purity of phosphoric acid being 85%; The Fe / P molar ratio of the first granular lithium iron phosphate is 0.965; The first carbon source is a combination of one or more of glucose, sucrose, and polyethylene glycol, and the amount of the first carbon source added is 0.4 wt% to 0.8 wt% of the carbon content in the first granular lithium iron phosphate; The first dopant is one or more of titanium dioxide, ammonium metavanadate, manganese pentoxide, niobium pentoxide and cerium oxide. The amount of the first dopant added is determined according to the proportion of one or more of titanium, vanadium, manganese, niobium and cerium elements in the first dopant in the first granular lithium iron phosphate being 3000ppm to 5000ppm.
3. The method for preparing a high-density lithium iron phosphate cathode material according to claim 1, wherein: In step 01: When wet grinding, it is carried out at 10°C to 45°C, the sand grinding particle size D50 is 0.7μm to 0.9μm, and the solid content is 30wt% to 50wt%; During spray drying, the feed temperature is 180°C to 240°C, the discharge temperature is 80°C to 140°C, the particle size D50 of the intermediate product obtained after spray drying is 20μm to 60μm, and the water content is ≤1.5%; During sintering, the sintering temperature is 780°C to 810°C and the sintering time is 6h to 10h under nitrogen atmosphere; The particle size D50 of the first lithium iron phosphate particles is 2.0 μm to 4.0 μm, and the average particle size of the first lithium iron phosphate particles is 2000 nm to 3000 nm.
4. The method for preparing a high-density lithium iron phosphate cathode material according to claim 1, wherein: In step 02: The Fe / P molar ratio of the in-situ doped iron phosphate is 0.970 to 0.980, and the specific surface area of the in-situ doped iron phosphate is 15m 2 / g to 25m 2 / g, the primary particle size of the in-situ doped iron phosphate is 40nm to 80nm; The doping element is Ti, and the in-situ doping amount of Ti is 5000ppm to 8000ppm; The purity of lithium carbonate is ≥99.5%, and the Li / Fe molar ratio of lithium carbonate is 1.01 to 1.04; The second carbon source is a mixture of one or more of glucose, sucrose, polyethylene glycol, and citric acid and one of urea, melamine, dicyandiamide, and thiourea, wherein the amount of the second carbon source added is 0.8 wt % to 1.2 wt % of the carbon content in the second granular lithium iron phosphate; Urea, melamine, dicyandiamide and thiourea are all raw materials of C3N4, and the carbon content in C3N4 accounts for 0.4wt% of the carbon content in the second granular lithium iron phosphate.
5. The method for preparing a high-density lithium iron phosphate cathode material according to claim 1, wherein: In step 02: Wet grinding is carried out at 10°C to 45°C, with a sand grinding particle size D50 of 0.15μm to 0.25μm and a solid content of 30wt% to 50wt%; The feed temperature of the spray drying is 180°C to 240°C, the discharge temperature is 80°C to 140°C, and the particle size D50 of the intermediate product obtained by the spray drying is 20 μm to 60 μm, and the water content is ≤1.5%; The sintering is carried out in a nitrogen atmosphere, the sintering temperature is 500° C. to 600° C., and the sintering time is 3 h to 7 h; The particle size D50 of the second granular lithium iron phosphate obtained after the airflow milling is 0.4 μm to 0.6 μm, and the average particle size of the second granular lithium iron phosphate is 80 nm to 160 nm.
6. The method for preparing a high-density lithium iron phosphate cathode material according to claim 1, wherein: In step 03: The third carbon source and the fourth carbon source are both polyvinyl pyrrolidone, and the addition amount of the third carbon source and the fourth carbon source accounts for 1.1wt% to 1.5wt% of the carbon content in the lithium iron phosphate positive electrode material; The wet grinding of the first slurry and the second slurry is carried out at 10° C. to 45° C., with a solid content of 30 wt % to 50 wt %, a sanding particle size D50 of the first slurry of 0.7 μm to 1.0 μm, and a sanding particle size D50 of the second slurry of 0.10 μm to 0.20 μm.
7. The method for preparing a high-density lithium iron phosphate cathode material according to claim 1, wherein: In step 04, the mass ratio of the first slurry to the second slurry is 5 to 7:3 to 5.
8. The method for preparing a high-density lithium iron phosphate cathode material according to claim 1, wherein: In step 04: The feed temperature of the spray drying is 180°C to 240°C, the discharge temperature is 80°C to 140°C, the particle size of the intermediate product is 20μm to 60μm, and the water content is ≤1.5%; The sintering process is carried out in a nitrogen atmosphere, the sintering temperature is 760°C to 780°C, and the sintering time is 6h to 8h; The particle size D50 of the lithium iron phosphate positive electrode material obtained after airflow milling is 0.9 μm to 1.2 μm.
9. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the preparation method of the high-density lithium iron phosphate positive electrode material according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises: a battery positive electrode made from the lithium iron phosphate positive electrode material according to claim 9.
Citation Information
Patent Citations
Preparation method of lithium iron phosphate positive electrode material, positive electrode plate and lithium ion battery
CN115863543A
Large-particle lithium iron phosphate / carbon composite material as well as preparation method and application thereof
CN117936749A
Preparation method of ultra-high-compaction lithium iron phosphate positive electrode material and lithium battery
CN118373398A
Lithium iron phosphate positive electrode material, preparation method thereof, positive plate and lithium ion battery
CN118610422A